Pengembangan LKS Berbasis STEM Pada Materi Reaksi Redoks Untuk Meningkatkan HOTS Siswa - Vira Junita; Gulmah Sugiharti (Proceedings Series of Educational Studies, 2023)
Abstract: This study's purpose to develop STEM-based Chemistry worksheets on Redox Reaction based in BSNP standards to student in X MAN DAIRI, look the HOTS improvement, find students responses to the worksheets. This worksheets created using the 4D method consist of Define (analysis of student needs), Design (design the product in accordance with student needs), Development which the stage of product development in the form of STEM based worksheet that was already practicable to use, and Dissemination which carried out to observe the increase in HOTS in students in terms of scores before and after students used worksheet. The data generated is formed of qualitative and quantitative data. The results of the qualitative data are in the form of an expert validator's assessment regarding the STEM based worksheet which is in accordance with the eligibility of the BSNP which is categorized as “very valid and does not need revision”. For student responses to STEMbased worksheets included the “good category”. Meanwhile, STEM-based worksheets contains practice questions based on the HOTS that consist “medium requirements”. Based on the study's findings, conclude that STEM-based worksheets on redox reactions produce positive student responses, conform to BSNP criteria, and can raise students' HOTS when used.Keywords: Student worksheet, STEM, HOTS, student responsesAbstrak: Tujuan dari penelitian ini adalah mengembangkan LKS Kimia berbasis STEM pada materi Reaksi Redoks yang sesuai dengan standar BSNP untuk meningkatkan HOTS siswa kelas X di MAN DAIRI serta mengetahui respon siswa terhadap LKS hasil pengembangan. LKS ini dikembangkan dengan menggunakan metode 4D yang terdiri dari Define (pendefinisian) berupa analisis kebutuhan siswa, Design (perancangan) berupa perancangan produk yang sesuai dengan kebutuhan siswa, Development (pengembangan) adalah tahap pengembangan produk berupa LKS berbasis STEM yang sudah layak untuk digunakan serta Disseminate (penyebaran) dilakukan untuk melihat peningkatan HOTS pada siswa ditinjau dari nilai sebelum dan sesudah siswa menggunakan LKS. Data yang dihasilkan dari penelitian ini berupa data kualitatif dan kuantitatif. Hasil dari data kualitatif berupa penilaian validator ahli terkait LKS berbasis STEM yang sesuai dengan kelayakan BSNP yang terkategori “sangat valid dan tidak perlu revisi”. Untuk respon siswa terhadap LKS berbasis STEM termasuk dalam kategori “baik”. Sedangkan data kuantitatifnya berupa latihan soal berbasis HOTS yang ada di dalam LKS berbasis STEM yang termasuk dalam kriteria “sedang”. Berdasarkan hasil penelitian ini dapat disimpulkan bahwa LKS berbasis STEM pada Materi Reaksi Redoks memberikan respon yang baik kepada siswa dan sudah sesuai dengan standar BSNP serta penggunaannya dapat meningkatkan HOTS siswa.Kata kunci: LKS, STEM, HOTS, respon siswa